1997
DOI: 10.1007/pl00006179
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolutionary Analysis of the Thiamine-Diphosphate-Dependent Enzyme, Transketolase

Abstract: Abstract. Members of the transketolase group of thiamine-diphosphate-dependent enzymes from 17 different organisms including mammals, yeast, bacteria, and plants have been used for phylogenetic reconstruction. Alignment of the amino acid and DNA sequences for 21 transketolase enzymes and one putative transketolase reveals a number of highly conserved regions and invariant residues that are of predicted importance for enzyme activity, based on the crystal structure of yeast transketolase. One particular sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 85 publications
3
59
0
Order By: Relevance
“…Furthermore, except for three synonymous substitutions, it is identical to the consensus sequence derived from the TK cDNA of controls and WK patients [17]. This sequence comparison further con®rms that the sequence submitted to GenBank by Singleton and collaborators contains four nonsynonymous substitutions, an observation which is supported by an alignment including TK sequences from rodents [23].…”
Section: Sequence and Sequence Comparisonsupporting
confidence: 59%
See 3 more Smart Citations
“…Furthermore, except for three synonymous substitutions, it is identical to the consensus sequence derived from the TK cDNA of controls and WK patients [17]. This sequence comparison further con®rms that the sequence submitted to GenBank by Singleton and collaborators contains four nonsynonymous substitutions, an observation which is supported by an alignment including TK sequences from rodents [23].…”
Section: Sequence and Sequence Comparisonsupporting
confidence: 59%
“…The coding region comprises 1869 nucleotides which are translated into a protein of 623 amino acid residues with a calculated subunit molecular weight of 67.8 kDa. Comparison of TK sequences from various species have revealed two regions of high homology [23]. The ®rst region, termed the ThDP-binding motif [11], is located between amino acid residues 154 and 177 and is found in all known ThDP-dependent enzymes.…”
Section: Sequence and Sequence Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…The sequences are taken from the multiple alignment of 22 TK sequences in Schenk et al [138]. Only four sequences representing mammalian (Hsa: human [138]), plant (Cpl3: Craterostigma plantagineum [4]), fungal (Sce: Saccharomyces cerevisiae [155]) and bacterial (Eco: Escherischia coli [152]) sources have been selected for illustration. The consensus sequence based on the entire alignment in Schenk et al [138] is shown; x can be any amino acid.…”
Section: Transketolase: a Thiamin Diphosphate Dependent Enzymementioning
confidence: 99%